Crushing Behavior of Woven Roving Glass-Epoxy Elliptical Composite Cones - Al-Kateb, Mohamed M. (2004)
Structure made from composite materials offers important characteristics such as weight reduction, design flexibility, and safety improvement. These composite materials provide higher or equivalent crash resistance as compared to their metallic counterparts and therefore find use in crashworthiness applications. The design of various transport vehicles such as automobiles and aircraft for crashworthiness requires collapse resistance of structural component and energy absorption characteristics during collision. This work examines the effects of composite elliptical cone vertex angles on crushing behaviour, energy absorption subjected to quasi-static compressive load, and the capability of natural fibre composite as filler material. The composite elliptical cone walls were fabricated from woven roving glass fibre with orientation of [0/90] and epoxy. Since natural fibre composite materials are increasingly being utilised in automotive parts for their relatively high strength and stiffness to weight and cost ratios, chopped oil palm frond fibres mixed with resin in the form of foam were used in this study as fillers. The composite elliptical cones with vertex angles varying from 0º to 24º in 6 increments fabricated for axial compression tests with the cone bottom end dimension of ab = 74mm (inner major radius) and bb = 53mm (inner minor radius); 165mm high and 5mm thick were fixed for all the specimens. Different cone vertex angles (β) of the elliptical cone resulted in different dimension of cone top end i.e. at (inner major radius) and bt (inner minor radius). The composite elliptical cones fabricated and tested were of six layers. Thirty specimens were fabricated, fifteen of which were filled with chopped oil palm frond fibres. The load-deformation and the energy-deformation relations as well as the deformation history and failure modes for the composite elliptical cones with various vertex angles tested under quasi-static axial crushing load are presented and discussed. The load-deformation curves presented were obtained from averaging the load-deformation points for three replicated tests with identical elliptical cone and testing conditions. In addition, the effects of cone vertex angles, filling on the load carrying capacity and the energy absorption capability are discussed. The results showed that the quasi-static axial crushing behaviour of elliptical woven roving laminated composite cones is strongly affected by their structural geometry, the specific energy absorbed by the composite elliptical cones with the vertex angles of 6º, 12º, 18º, and 24º, both the empty and the filled with natural fiber, which is more than that in an elliptical cone with the vertex angle of 0º (the elliptical tube) at any given deformation. On the other hand, empty core elliptical composite cones were better in specific energy absorption than those filled with natural fibre. The specific energy absorption for elliptical composite cone showed positive correlation i.e., the more the angle increases the more energy is absorbed. In this regard, the empty elliptical composite cone with 24º angle exhibited the best energy absorption capability.